Description of the larva of Telebasis griffinii (martin, 1896) (Zygoptera: Coenagrionidae) - Guillermo-Ferreira, R.; Bispo, P. C. [UNESP] (My University, 2013)
A description and illustrations of the final instar larva are provided based on reared specimens collected in Sâo Paulo State, Brazil. T. griffinii can be distinguished from other Telebasis species by the 6 palpal setae, 1 premental seta, no setae on antennae, and the shape of the foliaceous and lanceolate caudal lamellae.